368 Serum vitamin D levels and risk of musculoskeletal injury in university track and field athletes. (3rd March 2020) - Miller, Timothy; Harangody, Sarah; Kuzma, Scott; Magnussen, Robert
Abstract : Background: While vitamin D has been shown to be an important factor in muscle, tendon, and bone health, there is limited data on the relationship of serum vitamin D levels and injury risk in otherwise healthy collegiate athletes. Objective: To determine the prevalence of inadequate serum vitamin D levels in Division I collegiate athletes and risk of musculoskeletal injury in relation to vitamin D levels. Design: Retrospective review of injury tracking database records of track and field athletes at our institution was performed to collect age, race, serum vitamin D level, and injury history. Setting: Division I collegiate athletics. Patients (or Participants): Track and field athletes at our university who underwent serum vitamin D testing between October 2018 – February 2019. Interventions (or assessment of risk factors): Vitamin D level was measured using serum total 25-hydroxy vitamin D (25-OH vitamin D). Insufficient and deficient values were combined and labeled as 'inadequate' if they were measured to be less than 32 ng/mL. Information was collected for 34 athletes (13 males, 21 females). Main outcome measurements: Serum 25-OH vitamin D level and musculoskeletal injury history Results: Of the 34 athletes tested 14 were measured in the inadequate range (16.4 ng/mL to 29.4 ng/mL). 6 of 7 female sprinters and all male sprinters (n=2) fell in the inadequate range. Statistically significant correlation was demonstrated between race and vitamin D level with more black athletes demonstrating inadequate vitamin D levels (p=0.035). There was no statistical correlation between athletes sustaining injuries and having inadequate serum vitamin D levels. Conclusions: Among Division I collegiate track and field athletes there was no statistical correlation between inadequate serum vitamin D levels and musculoskeletal injury risk. There was a higher rate of inadequate serum vitamin D levels among black athletes. Future studies with larger numbers of athletes may demonstrate a correlation between low serum vitamin D levels and musculoskeletal injury rate.